Improving productivity of production line using lean manufacturing - Le, Tran Quynh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Reducing waste, cutting production costs, and raising productivity are the most important objectives for fast-moving consumer goods manufacturing to maintain competitiveness in the global market and aim for stable and long-term development. Lean manufacturing is a set of tools, processes, and concepts for implementing continuous improvement and eliminating operations that do not bring value to the business. This study emphasizes defining and evaluating overburden, monitoring process efficiency, and formulating improvement plans using the DMAIC framework in terms of lean implementation. Lean techniques such as 3M (Muda, Muri, Mura), and NVA (non-value-added) analysis are used to eliminate waste, reduce cost, and increase line productivity. After applying Lean Manufacturing with the suggested DMAIC framework, the packing system automation will replace the current system. The advantages of this innovation will increase the productivity of the production line. In addition, it can also improve industrial safety and ergonomic work conditions for workers and reduce labor.